Apparent diffusion coefficient measurements on a novel diffusion weighted MRI phantom utilizing EPI and HASTE sequences. (May 2020) - Kalaitzakis, Georgios; Boursianis, Themistoklis; Gourzoulidis, Georgios; Gourtsoyianni, Sofia; Lymperopoulou, Georgia; Marias, Konstantinos; Karantanas, Apostolos; Maris, Thomas G.
Highlights: Polyacrylamide gels are better in simulating ADC values compared to sucrose solutions used in this study. The coefficient of variation of polyacrylamide gels has lower values from sucrose solutions. Weighted Linear is faster than the Non Linear and equally precise for ADC measurements. The fitting method is a significant parameter in ADC measurements. An acceptance condition for precise ADC measurements is that SSNR should be higher than 5. Abstract: Purpose: The aim of this study is to introduce a novel DWI-MRI phantom and to compare Apparent Diffusion Coefficient (ADC) measurements, utilizing EPI-DWI and HASTE-DWI sequences and two different fitting algorithms. Materials and Methods: 23 test tubes with different sucrose concentrations and polyacrylamide gels were used as a phantom for ADC measurements. The phantom was scanned on a clinical MRI system (1.5 T) over a two-month period utilizing an EPI-DWI and a HASTE-DWI sequence. ADC maps were calculated using a Weighted Linear (WL) and a Non Linear (NL) fitting algorithm. Measurements were performed with two sequences and two fitting algorithms. Geometric Distortions (GD), Ghosting Ratios (GR) and Signal to Structured Noise Ratios (SSNRs) were estimated using both sequences from the resultant ADC parametric maps. Results: Polyacrylamide gels reveal lower coefficient of variation (CV%) as compared to sucrose solutions. ADC measurements performed with WL and NL algorithms reveal identical results with both sequences. WL and NL algorithms require approx. 3 s and 7 min respectively, for a single slice. EPI-DWI reveals a mean percent ADC value difference of (+4.5%) as compared to HASTE-DWI, regardless the type of fitting algorithm. Conclusion: Polyacrylamide gels can serve as a better means for simulating ADC values, compared with sucrose solutions used in this study. WL can be proposed as the method for ADC measurements in daily clinical practice. WL is significantly faster than NL fitting method and equally precise. SSNR measured directly on ADC maps is an excellent means for testing the precision of ADC measurements.